Estimation of Unobservable Variables in W8D-2010 Model - Gosińska, Emilia; Leszkiewicz-Kędzior, Katarzyna; Welfe, Władysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper presents the methods of calculation and estimates of unobservable variables, being an extension of the estimation database of the W8D-2010 model. The methodologies for estimating the total factor productivity, the human capital, the knowledge capital embodied in fixed assets and the potential GDP are discussed in some details. The alternative estimates of the natural rate of unemployment (NAWRU, NAIRU) are also made and compared. In addition, the expected life cycle income is calculated using information on the structure of employment by age.